Deiksis dalam Film “Ku Kira kau Rumah” : Analisis Pragmatik - Rizka Ardillah Ardillah; Kingkin Puput Kinanti; Luly Zahrotul Lutfiyah (IKIP Budi Utomo Malang, 2023)
This research is a discussion of pragmatic studies, namely deixis. deixis itself is a word that has no reference depending on what, who, where and when the speech occurs. The purpose of this research is 1) to explain the forms of deixis, 2) to explain the meaning of deixis, 3) to explain the function of deixis. the research data is in the form of the movie